Durable response to dual immune checkpoint blockade in Lynch syndrome–associated serous ovarian carcinoma: a case report - Mohamad Mourad; Nada Assaf; Layal Al Mahmasani; Rami Mahfouz; Najla Fakhruddin; Ali Shamseddine (Frontiers in Medicine, 2026)
Background Immune checkpoint inhibitors (ICIs) have demonstrated efficacy in microsatellite instability–high (MSI-H) or mismatch repair–deficient (dMMR) tumors. However, their role in dMMR serous ovarian cancer remains undefined, particularly when given without chemotherapy. Case description We report the case of a 42-year-old woman with a strong family history of malignancy who presented with metastatic high-grade serous ovarian carcinoma involving the liver, peritoneum, lymph nodes, and bone. Tumor immunohistochemistry demonstrated isolated loss of MSH2 expression. Germline testing confirmed a pathogenic MSH2 mutation, establishing a diagnosis of Lynch syndrome. Following multidisciplinary discussion, combined chemoimmunotherapy was recommended; however, the patient declined cytotoxic chemotherapy and was treated with dual immune checkpoint blockade (ipilimumab and nivolumab). Early imaging demonstrated a rapid and marked metabolic response, with subsequent scans confirming near-complete resolution of disease. The patient underwent interval cytoreductive surgery, which revealed minimal residual disease. Maintenance nivolumab and bevacizumab were initiated postoperatively. At latest follow up after 2 years, the patient remains in complete radiologic remission, with no evidence of active disease. Conclusion This case highlights the importance of comprehensive molecular profiling for patient selection and biomarker-guided treatment strategies in patients with Lynch syndrome. Despite the serous histology of the patient’s ovarian cancer, the presence of dMMR by immunohistochemistry and an underlying history of Lynch syndrome supported the use of a chemotherapy-free regimen with dual ICIs. Subsequent somatic next-generation sequencing revealed MSI-H/TMB-H disease, which explains the remarkable response that the patient had.